Effect of operating parameter on membrane distillation performance using kapok fibre for humic acid treatment - Zulkefli, Aina Syazwana (2021)
There is no doubt that in finding solution to the problem of fresh water scarcity and its high demand. Membrane distillation have been shown to be an effective alternative to replace conventional technologies which found uneconomical. As agricultural waste is abundantly available, kapok fibre has been chosen an alternative solution for synthetic membranes which not environmentally friendly. This study aims to determine the physical properties of raw kapok fibre in the membrane distillation system, to investigate the effect of operating parameters in membrane distillation for humic acid in terms of water permeability and rejection rate, and finally to determine the reusability of kapok fibre in the membrane distillation system. The physical properties of the raw kapok fibre have been determined with respect to morphology, absorption test, and water contact angle method. Then, it followed by investigating the performances of the kapok fibre through membrane distillation process with three different operating parameters. Next, reusability test was conducted through the membrane distillation system for about 20 hours. Characterisation test revealed the linkage structure of kapok fibre, the low increment of moisture content in the raw kapok fibre and the water contact angle exhibits 152.704°. Meanwhile, the first operating parameter used in membrane distillation system, which is the temperature of feed humic solution at 60°C has produced the highest permeate flux of 0.629 kg/m2h followed by 98.753 % of rejection at 40°C. Then, the lowest feed concentration of humic acid solution which 0.1 g/L showed the highest permeate flux of 0.634 kg/m2h followed by 97.47 % rejection rate. The 5 g of kapok fibre shows the highest permeate flux with 0.803 kg/m2h and 35g of kapok fibre shows highest rejection rate which 98.91%. The long-time operation has resulted in a slow decrease of permeate flux from 0.321 kg/hm2 to 0.089 kg/m2h after 20 hours. Therefore, the excellence hydrophobic property of the kapok fibre has successfully created an alternative solution for synthetic membrane studies in the membrane distillation process.